Conservation of apple and pear juice concentrates. Synergic effect of heat and radiation - Kaupert, Norma Lucía; Lescano, H. G.; Kotliar, Natalio (Organismo Internacional de Energía Atómica; Austria, 1981)
Fil: Kaupert, Norma Lucía Comisión Nacional de Energía Atómica; Argentina